Australian soil and land survey : field handbook (Australian soil and land survey handbook ;, 2009)
"This handbook specifies methods, standards and terminology used in soil and land survey investigations related to practical problems of land use and the scientific study of land and soil. It has been widely used and adopted as a standard throughout Australia, providing one reference set of definitions for the characterisation of landform and vegetation and for the description of soils. The book advocates that a comprehensive suite of land and soil attributes be recorded in a uniform manner. This approach is held to be more useful than the allocation of land or soil to preconceived types or classes. Its usefulness is enhanced where computer facilities are available. This revised edition contains significant changes to the Vegetation chapter and revisions to the Location chapter bringing it up-to-date with the use of Global Positioning Systems (GPS) and changes to the Substrate chapter relating to the regolith."--Provided by publisher.